Multiphase flow and fluidization : continuum and kinetic theory descriptions - Gidaspow, Dimitri, 1934- (Academic Press, 1994)
Useful as a reference for engineers in industry and as an advanced level text for graduate engineering students, Multiphase Flow and Fluidization takes the reader beyond the theoretical to demonstrate how multiphase flow equations can be used to provide applied, practical, predictive solutions to industrial fluidization problems. Written to help advance progress in the emerging science of multiphase flow, this book begins with the development of the conservation laws and moves on through kinetic theory, clarifying many physical concepts (such as particulate viscosity and solids pressure) and introducing the new dependent variable--the volume fraction of the dispersed phase. Exercises at the end of each chapterare provided for further study and lead into applications not covered in the text itself. Key Features * Treats fluidization as a branch of transport phenomena * Demonstrates how to do transient, multidimensional simulation of multiphase processes * The first book to apply kinetic theory to flow of particulates * Is the only book to discuss numerical stability of multiphase equations and whether or not such equations are well-posed * Explains the origin of bubbles and the concept of critical granular flow * Presents clearly written exercises at the end of each chapter to facilitate understanding and further study.